2015
DOI: 10.2174/2211555204666150702160805
|View full text |Cite
|
Sign up to set email alerts
|

Glucan Particles Loaded with Fluorinated Emulsions: A Sensitivity Improvement for the Visualization of Phagocytic Cells by <sup>19</sup>F-MRI

Abstract: A protocol to load perfluoro-crown-ether (PFCE) nanoemulsion directly into yeast-derived glucan particles (GPs) was developed. It was observed that the PFCE encapsulation did not affect the 19 F-MRI properties of the nanoemulsion that is currently in clinical trials. GPs loaded with PFCE nanoemulsion were taken up avidly by murine macrophages in vitro, resulting in a cellular uptake 150 % higher than the not GPs-entrapped nanoemulsion. Accordingly, a corresponding improvement in the 19 F-MRI detection of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Glucan particles were prepared as described. 3,6,7 Briefly, Saccharomyces cerevisiae of the Sigma1278b strain background was used. 37 The specific strain (PC538) is a typical wild-type (WT) strain with the following genotype: MATa ste4 FUS1-HIS3 FUS1-lacZ ura3-52, 38 and was used for all experiments in the study.…”
Section: Glucan Particles and Fe(tob) Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucan particles were prepared as described. 3,6,7 Briefly, Saccharomyces cerevisiae of the Sigma1278b strain background was used. 37 The specific strain (PC538) is a typical wild-type (WT) strain with the following genotype: MATa ste4 FUS1-HIS3 FUS1-lacZ ura3-52, 38 and was used for all experiments in the study.…”
Section: Glucan Particles and Fe(tob) Labelingmentioning
confidence: 99%
“…Targeting of macrophages has potential for delivering drugs to sites of inflammation that are characteristic of disease states including cancer or atherosclerosis. 3,4 In order to identify inflammation for diagnostic purposes, encapsulation of an imaging agent may permit tracking of the GP carrier. For example, dyes have been encapsulated in GPs to enable fluorescence imaging of the particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the GPs can effectively prevent enzymatic digestion and the immune clearance of the drug carrier when the drug reaches the target tissue/cell ( 51 ). Thus, the GPs enhance the stability of the drug delivery system and reduce the accumulation of drugs in the blood circulation ( 52 ).…”
Section: Discussionmentioning
confidence: 99%